« Qu’ouïr (ou plus...) dans dix (ou plus !) dandies queer (ou plus ?) : traverser l’épreuve de l’extérieur » - Gilbert Pham-Thanh (Cahiers Victoriens et Edouardiens)
This paper will explore the reception of the dandy as a figure of the Other in the extended corpus of British 19th-century literature. The approach is based on the constitutive distinctions of the now common trilogy of the stranger, the foreigner and the alien, to which will be added the polysemic notion of queerness in order to shift the focus to the field of masculinities studies. The analysis of the positions of narrators, characters and readers will form the main axis in this study of dandiacal otherness.